Mathematical modelling of factory fires - Chua, Wei Yang (Nanyang Technological University, 2023)
Over the years, sawdust fires and explosions have always been a constant mainstay as a serious threat towards the wood and timber industry. Despite that, the prominence of their dangers always somehow seems to take a back seat as compared to their glaring exposure to fire risks. One of the main obstacles that risk managers have to face in these related industries, is the lack of understanding behind the self-igniting conditions of the sawdust pile, so they can take the appropriate measures to prevent the fire hazard.